In-vitro investigations into endocytosis and silencing of siRNA-liposomes - ALSHEHRI, ABDULLAH ALI D (2017)
Recent research has focused on exploiting the small interfering ribonucleic acid (siRNA) molecule in cancer therapy. However, the main bottleneck in applying siRNA clinically is its effective delivery to the cytosol of target cell. To design and develop a well-characterised non-viral delivery system to transport siRNA efficiently into A549 (human epithelial lung cancer) cell culture, an siRNA delivery system based on cationic liposomes comprising cationic lipid, 3ß-[N-(N',N'- dimethylaminoethane)-carbamoyl] cholesterol (DC-Chol), and neutral lipid, dioleoylphosphatidylethanolamine (DOPE) was used. Initially, toxicity assays showed that cell viability and cell membrane integrity are highly dependent on the total lipid concentration applied. At the optimised dose of 1.0 mM, liposome formulations did not show considerable, irreversible cellular damage, while dramatically reduced cell metabolic activity (as measured by the MTS assay), marked cell membrane disruption (as measured by the LDH assay) and cell necrosis (as measured by the Annexin V/propidium iodide assay) were found to be associated with exposure to higher doses of cationic liposome formulations. No significant effect was observed for the different ratios of cationic lipid to nucleic acid in the tested range. The classical film hydration method resulted in a high level of siRNA liposomal encapsulation and stability within RNase, even at relatively low levels of cationic lipid, 3.125:1, as confirmed by gel retardation and the ultrafiltration centrifugation method. In A549 cell culture, siRNA-liposome formulations prepared at different lipid compositions and at selected lipid-siRNA ratios, showed a reasonable cellular uptake, as observed by flow cytometry and confocal microscopy. A dose response relationship between the siRNA concentration and silencing efficiency was observed. It was noticed that level of luciferase protein silencing is not necessary directly proportional to the extent of cellular uptake; rather the mechanism of endocytosis was suggested to dictate the level of silencing. Cell internalisation pathways were hence probed using a panel of pharmacological inhibitors. Clathrin-mediated, dynamin-dependent pathway, and macropinocytosis - all seem to be involved in the transport of the siRNA-cationic liposomes. It appears that the caveolae-mediated pathway had no important role in the uptake of this delivery system, although the ‘non-specificity’ in action of inhibitors that cause cholesterol depletion from the plasma membrane, and which significantly affected the internalisation process, makes the difficult to make definitive conclusions. The level of luciferase silencing in A549-Luc cells, where siRNA uptake is dominated by the clathrin pathway, can almost be doubled using the endosomolytic agent, chloroquine. This indirectly confirms involvement of clathrin-mediated pathway, and is probably due to this cationic liposome system lacking the capacity to escape from the acidic environment of the endosomes/lysosomes. Liposome-siRNA formulations targeting EGFR were used to examine the effect on cell proliferation in NSCLC using an in vitro model. The siRNA-liposome formulations were able to mediate EGFR silencing and to improve cell proliferation. This work therefore contributes to the understanding of the cellular mechanisms involved in the transfer of cationic siRNA-liposome across the cell membrane and has important implications in the area of nanotoxicology and nanocarrier-mediated drug delivery.